Sequestration of Exogenous Volatiles by Plant Cuticular Waxes as a Mechanism of Passive Associational Resistance: A Proof of Concept - Camacho-Coronel, Xicotencatl; Molina-Torres, Jorge; Heil, Martin (Frontiers in Plant Science, 2020)
Numerous plant-derived volatile organic compounds (VOCs) induce the expression of resistance-related genes and thereby cause an 'associational resistance' in neighbouring plants. However, VOCs can also be sequestered by plant cuticular waxes. In case that they maintain their biological activity, such sequestered VOCs could generate a 'passive' associational resistance that is independent of any gene expression in the receiver. As a proof of concept, we used major components of the cuticular wax layers of the tree, Parkinsonia praecox, and conidia of Colletotrichum lindemuthianum, a fungal pathogen that has not been reported to infect P. praecox. Wax layers were re-constituted on glass slides and exposed to each of 20 pure VOCs for 1 day and then to ambient air for 1 day or 15 days. Gas chromatography-mass spectrometry (GC-MS) analyses showed that all 20 VOCs were sequestered by the re-constituted wax layers. Exposure to 18 of the VOCs significantly inhibited the germination of C. lindemuthianum conidia on these wax layers after 1 day of exposure to ambient air. Four of the VOCs: 4Z-heptenol, farnesene, limonene, and 2E-decenal, inhibited germination rates to less than 25% of the controls. After 15 days, all VOCs were still detectable, although at strongly reduced concentrations, and no significant inhibition of conidial germination could be detected anymore. Exogenous VOCs can be sequestered by the components of plant cuticular waxes and maintain their biological activity, at least over a certain time span: an effect that could generate a transient 'passive associational resistance' to pathogens.